Membangun Sistem Informasi Penjualan Perhiasan Pada Toko Emas Sehati Ajibarang Berbasis Website - Candra Eka Wibowo; Ria Manurung; Dhany Faizal Racma (Electro Luceat, 2026)
Sehati Ajibarang Gold Shop faces challenges in its manual sales process, leading to inefficiencies, longer queues, and a higher risk of recording errors. This study aims to build a website-based jewelry sales information system to enhance operational efficiency, data accuracy, and reporting quality. The system was developed using the Prototype method with the Laravel framework, allowing iterative evaluation to ensure alignment with user requirements. Research findings indicate substantial improvements, as demonstrated by a Paired Sample T-Test, which revealed a decrease in average transaction processing time from 296.20 seconds to 50.60 seconds. Additionally, a performance assessment based on the ISO/IEC 25000 standard confirmed the system's high quality: Functional Suitability 97.07%, Performance Efficiency 96.63%, Usability 88.90%, and Security 92.23%. The system effectively automates business processes, reduces errors, and delivers rapid and accurate sales reports